Determination of the steroid profile in alternative matrices by liquid chromatography tandem mass spectrometry. Issue 197 (March 2020) - Gomez-Gomez, Alex; Miranda, Jezid; Feixas, Georgina; Arranz Betegon, Angela; Crispi, Fatima; Gratacós, Eduard; Pozo, Oscar J.
Graphical abstract: Highlights: A LC–MS/MS method for steroids quantification in alternative matrices is validated. The steroids endogenous range in saliva, breast milk and amniotic fluid is reported. Endogenous ranges of steroids in alternative matrices are reported for first time. Abstract: The simultaneous determination of a broad panel of steroids provides more accurate information about the hormonal status than the detection of a single hormone. For that reason, the determination of the steroid profile, i.e. the endogenous steroid hormones and their main metabolites, has become the most powerful tool for the study of hormonal imbalances. The usefulness of the evaluation of the steroid profile in urine and plasma is widely accepted. However, despite its broad potential applicability, the evaluation of the whole steroid profile in alternative matrices such as amniotic fluid, saliva and breast milk remains almost unexplored. In this research we developed and validated a liquid chromatography-tandem mass spectrometry (LC–MS/MS) method for the quantification of several steroids and their metabolites in amniotic fluid (28 analytes), saliva (15) and breast milk (12). Sample preparation, chromatographic conditions and mass spectrometric conditions (e.g. ionization species or ion source parameters) were optimized. The method was shown to be linear in the range of endogenous concentrations for all studied metabolites. Intra- and inter-assay accuracies were between 80% and 120% while intra- and inter-precisions were below 20% for all analytes in all matrices. The applicability of the method was evaluated by the comparison between the concentration ranges obtained in healthy volunteers (n = 30 per matrix) and the scarce data previously reported in literature. The concentration ranges for several analytes are reported for the first time. The present methodology represents a useful tool for the comprehensive evaluation of the steroid profile in alternative matrices and can be applicable for different clinical purposes.